Land-traffic crash leading to passenger vehicle submersion, drowning and other fatal injuries: A 44-year study based on records from the Finnish Crash Data Institute - Tikka Julius; Lunetta Philippe (Elsevier Ltd, 2022)
Background: Land motor traffic crash (LMTC) -related drownings are an overlooked and preventable causeof injury death. The aim of this study was to analyze the profile of water-related LMTCs involving passen-ger cars and leading to drowning and fatal injuries in Finland, 1972 through 2015.
Materials and methods: The database of the Finnish Crash Data Institute (FCDI) that gathers detailed information on fatal trafficaccidents provided records on all LMTCs leading to drowning during the study period and, from 2002 to2015, on all water-related LMTCs, regardless of the cause of death. For each crash, we considered vari-ables on circumstances, vehicle, and fatality profiles.
Results: During the study period, the FCDI investi-gated 225 water-related LMTCs resulting in 285 fatalities. The majority of crashes involved passengercars (124), and the cause of death was mostly drowning (167). Only 61 (36.5%) fatalities sufferedsome–generally mild–injuries. The crashes frequently occurred during fall or summer (63.7%), in a riveror ditch (60.5%), and resulted in complete vehicle’s submersion (53.7 %). Half of the crashes occurred inadverse weather conditions and in over 40% of the cases, the driver had exceeded the speed limit. Amongdrivers, 77 (68.8%) tested positive for alcohol (mean BAC 1.8%).
Conclusion: Multidisciplinary investiga-tions of LMTCs have a much higher potential than do exclusive police and medico-legal investigations.The risk factors of water-related LMTCs are similar to those of other traffic crashes. However, generallythe fatal event in water-related LMTC is not the crash itself, but drowning. The paucity of severe physicalinjuries suggests that victims’ functional capacity is usually preserved during vehicle submersion.
Practical Applications: In water-related LMTCs, expansion of safety measures is warranted from generaltraffic-injury prevention to prevention of drowning, including development of safety features for sub-merged vehicles and simple self-rescue protocols to escape from a sinking vehicle.
The Author(s). Published by Elsevier Ltd. This is an open access article under the CC BY license(http://creativecommons.org/licenses/by/4.0/).